Post-testicular spermatozoa of a marine teleost can conduct de novo cytoplasmic and mitochondrial translation - Júlia Castro-Arnau; François Chauvigné; Asier González; Roderick Nigel Finn; Montserrat Carrascal; Joan Cerdà (iScience)
Summary: Translational silence of spermatozoa has long been considered the norm in animals. However, studies in mammals have shown that the mitochondrial ribosomal machinery is selectively activated during capacitation in the female reproductive tract, while cytosolic ribosomes remain inactive. Here, using quantitative proteomics in a piscine model species, we show that proteins involved in mRNA processing and cytoplasmic translation are predominantly accumulated in immature spermatozoa within the extratesticular excurrent ducts, while those related to flagellar motility are enriched in ejaculated (mature) sperm. Based upon in vitro incubation of isolated spermatozoa, motility assays and polysome profiling, we further show that 80S cytoplasmic and 55S mitochondrial ribosomes are actively involved in the translation of motility- and osmoadaptation-related proteins. These findings thus reveal that post-testicular piscine spermatozoa can maintain de novo protein synthesis through both mitochondrial and cytoplasmic ribosomal activity, which is necessary for the acquisition of full sperm function.